(untitled) (Journal of the College of Education for Women, 2019)
Learn new methods of teaching mathematics contribute to raising the level of pupils to acquire mathematical concepts primary stageAttempt advancement in the level of mathematics teaching for the better through the use of modern teaching strategies. The research aims at the progress in the acquisition of mathematical concepts schoolgirls after subjecting the fourth grade to teach in active learning strategies, the number of research sample (60) schoolgirl, by (30) schoolgirl experimental group and 30 pupils of the control group. Clear from the results shown the presence of a statistically significant difference between the acquisition of concepts of schoolgirls two groups (experimental and control) for the benefit of pupils of the experimental group who studied using active learning at the level of (0.05) in the Test acquire concepts, which was after the end of the experiment directly